STUDI TENTANG MINAT MAHASISWA JURUSAN PENDIDIKAN IPS MEMILIH FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN DI UNIVERSITAS RIAU - Sardila Sardila; Ahmad Eddison; Separen Separen (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
: This research was motivated by the interest of students majoring in Social Studies Education who studied at FKIP, Riau University. Where students pursuing higher education at the FKIP Faculty are supposed to be teachers, it turns out that not all students studying at FKIP are interested in becoming teachers. But there are several factors for them to study at FKIP Riau University. The formulation of the problem in this study is how is the interest of students majoring in social studies in choosing FKIP at the University of Riau? And what are the factors that students choose FKIP at the University of Riau?. The purpose of this study is to find out how the interest of students majoring in Social Sciences in choosing FKIP at the University of Riau and to find out what are the factors that make students majoring in Social Sciences choose FKIP at Riau University. The benefit of the results of this study is a source of learning for all parties, especially for prospective students who want to continue their education to college by considering their interest in studying at a university. This research method is descriptive quantitative, the data collection instrument used in this research is a questionnaire consisting of 9 indicators with 19 statements. The population in this study were active students majoring in Social Studies Education, amounting to 939 people. The sample in this study was taken using the Non Probity Sampling technique, more precisely the quota sampling technique of 60 people. Based on the results of the study, it can be concluded that overall the data regarding the "Study of Interests of 60 samples of Social Studies Education Department Students Choosing FKIP at the University of Riau" is in the "Good" category. Respondents answered Strongly Agree (SS) plus Agree(S) namely 14.12% + 39.47% = 53.59%, this is in the range of 50.01%-75%. Thus, it can be concluded that the interest of 60 samples of Social Sciences Education Department Students in choosing FKIP at the University of Riau is at the "Good" level.Key Words: Interest, Student, FKIP